2013
DOI: 10.1186/1756-3305-6-189
|View full text |Cite
|
Sign up to set email alerts
|

American tegumentary leishmaniasis caused by Leishmania (Viannia) braziliensis: assessment of parasite genetic variability at intra- and inter-patient levels

Abstract: BackgroundThe genetic variability of Leishmania (Viannia) braziliensis was assessed at intra and interpatient levels of individuals with different clinical manifestations of American tegumentary leishmaniasis (ATL).MethodsFifty-two samples, of which 13 originated from cutaneous lesions and 39 from mucosal lesions, provided by 35 patients, were examined by low-stringency single-specific-primer PCR (LSSP-PCR) and phenetic analysis. Genetic variability of L. (V.) braziliensis, in kinetoplast DNA (kDNA) signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…It is uncertain if the genetic variability observed in L. (V.) braziliensis populations is an important factor affecting the therapeutic outcome 48,49 . Results from our study and other studies 30,34,35 indicate that the L. (V.) braziliensis population endemic to the state of Rio de Janeiro presents a homogeneous genetic pattern with low variability, which could explain the favorable therapeutic response to MA observed in patients who were infected in this state. However, therapeutic response to antimonial drugs may vary in states other than Rio de Janeiro, where ATL may be caused by different Leishmania species or by an L. (V.) braziliensis subpopulation with a high genetic variability 6,8,50 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is uncertain if the genetic variability observed in L. (V.) braziliensis populations is an important factor affecting the therapeutic outcome 48,49 . Results from our study and other studies 30,34,35 indicate that the L. (V.) braziliensis population endemic to the state of Rio de Janeiro presents a homogeneous genetic pattern with low variability, which could explain the favorable therapeutic response to MA observed in patients who were infected in this state. However, therapeutic response to antimonial drugs may vary in states other than Rio de Janeiro, where ATL may be caused by different Leishmania species or by an L. (V.) braziliensis subpopulation with a high genetic variability 6,8,50 .…”
Section: Discussionsupporting
confidence: 59%
“…Some authors suggested that different ATL clinical forms, including localized or disseminated leishmaniasis, are caused by distinct L. (V.) braziliensis subpopulations distributed among various locations of the state of Bahia 8,31,32 . Previous studies performed in Rio de Janeiro observed no association between Leishmania's genotypic patterns and the clinical manifestations or therapeutic responses 33,34,35 .…”
Section: Discussionmentioning
confidence: 81%
“…According to WHO, the CL clinical forms include localized, disseminated, diffuse, and atypical cutaneous and mucocutaneous leishmaniases 12 . Many factors can influence the clinical manifestations and prognosis of leishmaniasis, such as the immune response of the patient and the species of the parasite 1 , 13 . The parasite was identified as L. (V.) braziliensis, a prevalent species in southern Brazil and widely distributed in the country 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Шкірний лейшманіоз, що зумовлений Leishmania mexicana, розглядають як антропоноз або синантропний зооноз, де резервуаром збудника є собаки. Для патологічного процесу, котрий викликаний Leishmania mexicana, характерні по-одинокі виразки, які за умов сприятливого перебігу можуть рубцюватись протягом року [13,14]. Діагноз шкірного лейшманіозу підтверджується клініч-ною симптоматикою і виявленням збудника в уражених ділянках шкіри (мікроскопія і біопсія) [15].…”
Section: случай завозного кожного лейшманиоза в запорожьеunclassified